2017
DOI: 10.21037/tlcr.2017.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Volume versus diameter assessment of small pulmonary nodules in CT lung cancer screening

Abstract: Currently, lung cancer screening by low-dose chest CT is implemented in the United States for high-risk persons. A disadvantage of lung cancer screening is the large number of small-to-intermediate sized lung nodules, detected in around 50% of all participants, the large majority being benign. Accurate estimation of nodule size and growth is essential in the classification of lung nodules. Currently, manual diameter measurements are the standard for lung cancer screening programs and routine clinical care. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 47 publications
1
48
0
1
Order By: Relevance
“…The model reported in this paper is novel, as it incorporates screen detected nodule volume in the risk prediction calculation. Nodule volume is considered to be more accurate and reproducible than diameter measurements, 39 but its role in lung risk prediction models from clinical trial data has not been previously been used. A previous effort has been made to develop pulmonary risk model incorporating volume in a small cohort from one center, of 221 patents with a 37% malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The model reported in this paper is novel, as it incorporates screen detected nodule volume in the risk prediction calculation. Nodule volume is considered to be more accurate and reproducible than diameter measurements, 39 but its role in lung risk prediction models from clinical trial data has not been previously been used. A previous effort has been made to develop pulmonary risk model incorporating volume in a small cohort from one center, of 221 patents with a 37% malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical diagnosis of whether a nodule has shown growth or not is based on manual diameter measurements (21). The cutoff-value for evaluating an increase or decrease in the longest diameter in a clinical setting was set as 1.73 mm in the present study, based on the 95% limits of small non-calcified pulmonary nodules (24).…”
Section: Evaluation Of An Increase or Decrease In Volume Of Solid Nodmentioning
confidence: 99%
“…Although many volumetry studies have evaluated pulmonary solid nodules (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), the standard for the followup of pulmonary solid nodules in CT screening in the US and in daily clinical practice is still the measurement of pulmonary nodule size using electronic calipers (19,20). A review article concluded that accumulating evidence indicates that semi-automatic volume measurements have a higher accuracy and reproducibility than diameter measurements (21). To our knowledge, only one article has reported volume changes in clinically stable solid nodules with long-term CT follow-up (14).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the performance of volumetric measurements is highly dependent on the employed techniques. Using different types of volumetric techniques other investigators have previously shown volumetric measurements to be superior to linear measurements and therefore further studies regarding the value of alternative volumetric measurement techniques are warranted (11,16).…”
Section: Editorialmentioning
confidence: 99%